2020
DOI: 10.5194/acp-20-7021-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes dominate monoterpenes in northern wetland emissions

Abstract: Abstract. We have studied biogenic volatile organic compound (BVOC) emissions and their ambient concentrations at a sub-Arctic wetland (Lompolojänkkä, Finland), which is an open, nutrient-rich sedge fen and a part of the Pallas-Sodankylä Global Atmosphere Watch (GAW) station. Measurements were conducted during the growing season in 2018 using an in situ thermal-desorption–gas-chromatograph–mass-spectrometer (TD-GC-MS). Earlier studies have shown that isoprene is emitted from boreal wetlands, and it also turned… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
5
22
1
1
Order By: Relevance
“…5) than to surface temperature. At the same Stordalen wetland as our study, Holst et al (2010) found a steep temperature response to air temperatures above 15 • C, in agreement with our results ( Fig. 5) and previous high-latitude studies (Kramshøj et al, 2016;Lindwall et al, 2016a, b;Rinnan et al, 2014).…”
supporting
confidence: 94%
See 3 more Smart Citations
“…5) than to surface temperature. At the same Stordalen wetland as our study, Holst et al (2010) found a steep temperature response to air temperatures above 15 • C, in agreement with our results ( Fig. 5) and previous high-latitude studies (Kramshøj et al, 2016;Lindwall et al, 2016a, b;Rinnan et al, 2014).…”
supporting
confidence: 94%
“…Regarding methanol, EC fluxes investigated at the Stordalen mire wetland by Holst et al (2010) reached a noontime average hourly maximum of 1.3 nmol m −2 s −1 in early August, which is higher than our 0.2 nmol m −2 s −1 in July (Fig. 3).…”
contrasting
confidence: 74%
See 2 more Smart Citations
“…Other experiments in nearby Abisko heaths, mentioned above, documented sesquiterpene flux rates similar to those of monoterpenes measured in the same study (Faubert et al, 2010a;Valolahti et al, 2015). Most recently, sesquiterpenes have been detected as the main terpenoid emissions after isoprene at a subarctic wetland in Finland (Hellén et al, 2020). One obvious reason for our lack of sesquiterpene signal is that our flux footprint did not include a significant amount of high-emitting species since, for example, most of the nearby birch patches were outside of it.…”
Section: Fen Voc Fluxessupporting
confidence: 72%